2011
DOI: 10.5539/jas.v3n1p78
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Supplemental Irrigation and Applied Nitrogen on Wheat Water Productivity and Yields

Abstract: A field experiment was conducted for three growing seasons to study the effects of seasonal water use and applied N fertilizer on yield attributes and water productivity indices of wheat in an arid region of Iran. The results revealed that yield attributes were significantly affected by irrigation and nitrogen treatments and growing season, and their interactions. Crop height, maximum leaf area index and biological yields were increasingly affected by the available water and N fertilizer. The findings indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Limited irrigation is an important constraint for wheat production in rainfed, tropical, arid, and semi-arid regions. In scarce rainfall conditions and less irrigation, the best management option for N and irrigation levels is to maintain the maize-wheat cropping sequence [7] and limited irrigation water is combined with N fertilizer [8] to get maximum productivity of wheat. Supplemental irrigation significantly increased the yield of wheat with respect to rainfed treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Limited irrigation is an important constraint for wheat production in rainfed, tropical, arid, and semi-arid regions. In scarce rainfall conditions and less irrigation, the best management option for N and irrigation levels is to maintain the maize-wheat cropping sequence [7] and limited irrigation water is combined with N fertilizer [8] to get maximum productivity of wheat. Supplemental irrigation significantly increased the yield of wheat with respect to rainfed treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that drought is a main limiting factor affecting growth and plant biomass under semi-arid conditions (Abdel-Ghani, 2013;Al-Rjoub et al, 2006). Under limited water conditions, irrigation scheduling is used to allocate irrigation water rationally during different wheat growing stages in order to maximize GY and WP (Montazar et al, 2011). Similarly, many authors (Erekul et al, 2012;Semcheddine et al, 2014;Shang et al, 2020) showed the importance of SI to increase yield under water limiting environments.…”
Section: Effect Of Supplemental Irrigation On Yield and Agronomictraitsmentioning
confidence: 99%
“…SI is used to improve and stabilize crop yield by supplying the crop with water by SI when rainfall is limited to provide sufficient moisture for normal plant growth (Oweis, 1997;Shang et al, 2020;Wang, 2017). Under limited rainfed conditions, irrigation scheduling is used to allocate irrigation water rationally during the critical growth stages to increase crop yield, and farm profit (Montazar et al, 2011). Therefore, selecting high-yielding varieties and using suitable agricultural practices in wheat production are considered major for wheat growers in Jordan to enhance grain yield under dry farming.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of SI applications and its economic gains in rainfed crops are well established at the field level (Oweis & Hachum, 2001, 2009; Zoebl, 2006; Montazar & Mohseni, 2011; Sui et al ., 2014; Shahi Nezhad & Pezeshkpour, 2015; Kahraman et al ., 2016; Manning et al ., 2018). Potential application and economic impact at the basin level are less researched.…”
Section: Introductionmentioning
confidence: 99%